Dynamic Properties of Soil in UAE from Field and Laboratory Tests - Khalil, Ahmed Mohsen (2020)
A Master of Science thesis in Civil Engineering by Ahmed Mohsen Khalil entitled, “Dynamic Properties of Soil in UAE from Field and Laboratory Tests”, submitted in December 2020. Thesis advisor is Dr. Zahid Khan and thesis co-advisor is Dr. Magdi El Emam. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).